2015
DOI: 10.1021/acs.jpcc.5b01373
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Transport Properties of Na[N(SO2F)2]–[N-Methyl-N-propylpyrrolidinium][N(SO2F)2] Ionic Liquids for Na Secondary Batteries

Abstract: Understanding ion transport in electrolytes is crucial for fabricating high-performance batteries. Although several ionic liquids have been explored for use as electrolytes in Na secondary batteries, little is known about the transport properties of Na + ions. In this study, the thermal and transport properties of Na[FSA]-[C 3 C 1 pyrr][FSA] (FSA − : bis(fluorosulfonyl)amide and C 3 C 1 pyrr + : N-methyl-Npropylpyrrolidinium) ionic liquids were investigated in order to determine their suitability for use as el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
121
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 117 publications
(147 citation statements)
references
References 43 publications
15
121
3
Order By: Relevance
“…Organic electrolytes have been applied as electrolytes for Na secondary batteries owing to its high electrochemical stability . Ionic liquids (ILs) composed of only cations and anions have low flammability, low volatility, and high thermal stability, which allow for improved safety characteristics of energy storage devices, and have been investigated as possible electrolytes for Na secondary batteries . Several groups have shown better performance with ILs compared to organic electrolytes in terms of cycle performance and rate capability.…”
Section: Figurementioning
confidence: 99%
“…Organic electrolytes have been applied as electrolytes for Na secondary batteries owing to its high electrochemical stability . Ionic liquids (ILs) composed of only cations and anions have low flammability, low volatility, and high thermal stability, which allow for improved safety characteristics of energy storage devices, and have been investigated as possible electrolytes for Na secondary batteries . Several groups have shown better performance with ILs compared to organic electrolytes in terms of cycle performance and rate capability.…”
Section: Figurementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Sodium is abundant in the crust and seawater, showing a relatively low standard redox potential (¹2.71 V vs. SHE). Thus, batteries with low cost and high energy density can be constructed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ionic liquids are inherently safe due to their negligible volatility and non-flammability, with some of them showing reasonably high ionic conductivities and wide electrochemical windows. 5,6 We have already reported that Na[TFSA]-Cs[TFSA] (TFSA = bis(trifluoromethylsulfonyl)amide) and Na[FSA]-K[FSA] (FSA = bis(fluorosulfonyl)amide) ionic liquids are promising electrolytes for sodium secondary batteries operating at an intermediate temperature range (>353 K). [1][2][3][4] However, these salts are solid at room temperature, while electrolytes with lower melting points are more desirable for the construction of batteries for a wide range of practical applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 The physical and electrochemical properties of ILs in Na secondary batteries have been studied in recent works. [8][9][10][11][12] In real application, polymerization of the IL is one important technique to retain the advantages of ILs and avoid leakage. As a type of gel polymer electrolytes (GPE), the resulting "ionic liquid polymer electrolytes (ILPEs)" consists of ILs, the host polymer, and another component for electrochemical reactions (e.g alkali metal salt).…”
mentioning
confidence: 99%